THERMODYNAMIC ANALYSIS OF THE HEAT BALANCES OF GEOCHEMICAL PROCESSES - Chudnenko K.V.; Karpov I.K. (My University, 1990)
In this paper we present a new method of analyzing the heat balances of complex chemical reactions in multicomponent systems; the method is a natural extension of the approach to physicochemical modeling as a problem of mathematical programming that we developed earlier. This approach is not confined to specific reactions (whose mechanisms and sequence often cannot be determined reliably enough), but deals with the overall process by which the system passes from a higher to a lower energy level. The calculation procedure involves an energy analysis of the thermal process, using the formalism of equilibrium chemical thermodynamics. The method described above can be used for the investigation of thermal processes in a wide variety of geochemical systems.